Concept of “Educational Efficiency” in Context of Inclusive Trends of Modern School - I. S. Samokhin; M. G. Sergeyeva; N. L. Sokolova; E. A. Mrachenko (Научный диалог)
The research urgency is caused by the essence of an inclusive approach to education, which assumes the achievement of all pupils a positive result at minimal psychological cost. The concepts of “efficiency” and “effectiveness of education” enshrined in domestic economic and pedagogical dictionaries are analyzed. It is established that the concept of “educational efficiency” used in pedagogy is based not on economic, but on general meaning of the word efficiency . It is shown that the educational efficiency is associated with performance, effectiveness, quality of the educational process, not with the ratio of the achieved pedagogical results with those or other cost (financial, human, chronological, etc.). At the same time, it is noted that almost all interpretations of the concept of “educational efficiency” correlate with economic definitions of the term efficiency in their structure. The fundamentals of I. S. Samokhin’s author conception, according to which the efficiency of the school inclusive education is based on a hierarchy of resources. The novelty of the study is to present the position according to which all students’ resources are divided into inviolable (health, emotional well-being, harmony in relationships with people), and those that can be spent in any amount (time, energy, freedom), if it does not affect resources of the first category.